Sputtering target for gas barrier coating, gas barrier coating and gas barrier film
A sputtering target with 40 to 90% silicon content addresses the refractive index mismatch and harmful gas issues in gas barrier film production, achieving a medium refractive index and improved barrier properties for display applications.
Patent Information
- Application Number
- JP2022188454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2022-11-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-25
AI Technical Summary
Conventional methods for manufacturing gas barrier films using plasma CVD require harmful silane gas, and the refractive index mismatch between gas barrier films and resin layers in display applications necessitates a different fabrication approach.
A sputtering target comprising metal and silicon, with a silicon content of 40 to 90% by mass, is used to produce a gas barrier film with a medium refractive index suitable for display applications, employing a sputtering method that avoids silane gas and results in an amorphous structure with improved barrier properties.
The sputtering method produces a gas barrier film with a refractive index of 1.5 to 1.7, suitable for display applications, exhibiting excellent gas barrier properties and reducing conductive paths through crystallinity, with a water vapor transmission rate of 1×10^-1 g/m^2/day or less.
Smart Images

Figure 0007611589000018 
Figure 0007611589000019 
Figure 0007611589000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a sputtering target for a gas barrier coating, a gas barrier coating, and a gas barrier film. More specifically, the present invention relates to a sputtering target for a gas barrier coating, a gas barrier coating, and a gas barrier film for forming a gas barrier coating having a medium refractive index and barrier properties by a sputtering method without using a CVD method using a silane gas, and the gas barrier coating and film. [Background technology]
[0002] Conventionally, a method for producing a gas barrier film in which a silicon carbide oxide film (SiOC) is formed on a substrate by a plasma CVD method has been disclosed (for example, Patent Document 1). The SiOC film has a refractive index in the range of 1.5 to 1.7. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-219427 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the CVD method employed in the manufacturing method described in Patent Document 1 must use harmful and highly toxic silane gas. Meanwhile, in display applications such as organic EL and electronic paper, a gas barrier film is laminated on the display to prevent the intrusion of gas, moisture, and the like from the outside. These displays also have a hard coat layer, an overcoat layer, and the like laminated thereon. These layers are generally resin layers, and have a refractive index of about 1.5 to 1.7 (referred to as a medium refractive index). Therefore, the refractive index of the gas barrier film used in display applications is also required to be small in difference from the refractive index of the resin layer.
[0005] The present invention has been made in view of the above-mentioned conventional inventions, and has an object to provide a sputtering target for a gas barrier layer, a gas barrier layer, and a gas barrier film for forming a gas barrier layer that exhibits a medium refractive index and has barrier properties by a sputtering method without using a CVD method using silane gas. [Means for solving the problem]
[0006] The sputtering target for a gas barrier layer, the gas barrier layer, and the gas barrier film of the present invention mainly include the following components.
[0007] (1) A sputtering target for a gas barrier film, comprising a metal and silicon, the content of the silicon being 40 to 90 mass% based on the total amount of the metal and the silicon, and the metal comprising any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr and Zn-Al (an alloy of Zn and Al).
[0008] According to such a configuration, the sputtering target for gas barrier films can be used to produce a gas barrier film having a medium refractive index suitable for display applications, etc., by performing a sputtering method.
[0009] (2) A gas barrier film comprising a metal oxide and a silicon oxide, the content of the silicon oxide being 60 to 90 volume % based on the total amount of the metal oxide and the silicon oxide, and the metal constituting the metal oxide being any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr and Zn-Al (an alloy of Zn and Al).
[0010] According to such a configuration, the gas barrier film exhibits a medium refractive index and is suitable for use in displays and the like.
[0011] (3) The gas barrier film according to (2), which has a refractive index of 1.5 to 1.7 for light with a wavelength of 550 nm.
[0012] According to such a configuration, the gas barrier film exhibits a medium refractive index and is suitable for use in displays and the like.
[0013] (4) The gas barrier film according to (2) or (3), which has no peaks derived from crystals when measured by X-ray diffraction.
[0014] With such a configuration, the gas barrier film has a non-crystalline (amorphous) structure, which reduces the number of conduction paths for moisture and gas between crystals due to the crystallinity, thereby further improving the gas barrier properties.
[0015] (5) A gas barrier film comprising, in this order, a substrate, an undercoat layer, and the gas barrier layer according to any one of (2) to (4).
[0016] According to such a constitution, the gas barrier film exhibits a medium refractive index and is suitable for use in displays and the like.
[0017] (6) Water vapor permeability is 1×10 -1 (g / m 2 / day) or less.
[0018] With this configuration, the gas barrier film exhibits excellent gas barrier properties. Effect of the Invention
[0019] According to the present invention, it is possible to provide a sputtering target for a gas barrier layer, a gas barrier layer, and a gas barrier film for forming a gas barrier layer that exhibits a medium refractive index and has barrier properties by a sputtering method without using a CVD method using silane gas. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a graph showing the results of crystallinity analysis of a gas barrier film. [Diagram 2] FIG. 2 is a graph showing the results of crystallinity analysis of the gas barrier film. [Diagram 3] FIG. 3 is a graph showing the results of crystallinity analysis of the gas barrier film. [Figure 4] FIG. 4 is a graph showing the results of crystallinity analysis of the gas barrier film. [Diagram 5] FIG. 5 is a graph showing the relationship between the silicon oxide content and the refractive index. [Figure 6] FIG. 6 is a graph showing the relationship between the silicon content and the refractive index. [Figure 7] FIG. 7 is a graph showing the relationship between the silicon oxide content and the water vapor transmission rate. [Figure 8] FIG. 8 is a graph showing the relationship between the silicon oxide content and the water vapor transmission rate. [Figure 9] FIG. 9 is a graph showing the relationship between the silicon oxide content and the water vapor transmission rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] <Sputtering target> A sputtering target according to one embodiment of the present invention includes a metal and silicon. The content of silicon relative to the total amount of the metal and silicon is 40 to 90 mass%. The metal includes any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr, and Zn-Al (an alloy of Zn and Al). Each of these will be described below.
[0022] The sputtering target of this embodiment preferably contains metal and silicon in a total amount of 99% by mass or more, more preferably 99.5% by mass or more. The sputtering target may contain other components as appropriate depending on the purpose, as long as the effect of this embodiment is achieved. In addition, the sputtering target may contain impurities that are inevitably mixed in.
[0023] The silicon content relative to the total amount of metal and silicon may be 40% by mass or more. The silicon content relative to the total amount of metal and silicon may be 90% by mass or less. If the silicon content is less than 40% by mass, the SiO2 content in the gas barrier film formed using the sputtering target is low, and the refractive index is greater than 1.7. On the other hand, if the silicon content exceeds 90% by mass, the SiO2 content in the gas barrier film formed using the sputtering target is high, and the refractive index is less than 1.5.
[0024] The method for producing the sputtering target of the present embodiment is not particularly limited. For example, the sputtering target can be produced by a conventionally known powder sintering method or the like.
[0025] The obtained sintered body is processed into a desired shape using a lathe or the like to produce the sputtering target of this embodiment. The target shape is not particularly limited. For example, the shape of the sputtering target is a flat plate (including a disk or rectangular plate), a cylindrical shape, or the like.
[0026] The sputtering target of the present embodiment can be formed on a predetermined substrate or film by sputtering using a magnetron sputtering device, thereby forming a gas barrier film (sputtered film).
[0027] As described above, according to this embodiment, the sputtering target can be used to produce a gas barrier film with a medium refractive index (n=1.5 to 1.7) suitable for display applications, by performing a sputtering method using this sputtering target.
[0028] <Gas barrier film> The gas barrier film of an embodiment of the present invention includes a metal oxide and a silicon oxide. The content of the silicon oxide with respect to the total amount of the metal oxide and the silicon oxide is 60 to 90% by volume. The metal constituting the metal oxide includes any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr, and Zn-Al (an alloy of Zn and Al). Each will be described below.
[0029] The metal contained in the metal oxide includes any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr, and Zn-Al (an alloy of Zn and Al). Such metal oxides are ZnO, TiO2, Nb2O5, AZO (ZnAlO), Cr2O3, Al2O3, Ta2O5, WO3, etc. Since the gas barrier film of this embodiment contains, for example, ZnO and a silicon oxide, the contained elements are Zn, Si, and O. For simplicity, it is hereinafter denoted as ZnSiO. Similarly, a gas barrier film containing TiO2 and a silicon oxide is denoted as TiSiO, a gas barrier film containing Nb2O5 and a silicon oxide is denoted as NbSiO, a gas barrier film containing AZO (ZnAlO) and a silicon oxide is denoted as ZnAlSiO, a gas barrier film containing Cr2O3 and a silicon oxide is denoted as CrSiO, a gas barrier film containing Al2O3 and a silicon oxide is denoted as AlSiO, a gas barrier film containing Ta2O5 and a silicon oxide is denoted as TaSiO, and a gas barrier film containing WO3 and a silicon oxide is denoted as WSiO.
[0030] In the description of the above gas barrier film, the valences are omitted. That is, for example, ZnSiO simply indicates that Zn, Si, and O are contained, and does not indicate that Zn, Si, and O have the same valence. The gas barrier film of this embodiment can take various valences and is not particularly limited.
[0031] The silicon oxide in the gas barrier film of this embodiment, when described by a chemical formula, refers to SiO2 or SiOx (1 < x < 2).
[0032] The gas barrier film of this embodiment preferably contains 99% by mass or more of metal oxide and silicon oxide in total, more preferably 99.5% by mass or more. The gas barrier film may contain other components as appropriate depending on the purpose, so long as the effects of this embodiment are achieved. The gas barrier film may also contain impurities that are inevitably mixed in.
[0033] The content of silicon oxide with respect to the total amount of metal oxide and silicon oxide may be 60% by volume or more. The content of silicon oxide with respect to the total amount of metal oxide and silicon oxide may be 90% by volume or less. If the content of silicon oxide is less than 60% by volume, the content of SiO2 in the gas barrier film is small, and the refractive index is greater than 1.7. On the other hand, if the content of silicon oxide is more than 90% by volume, the content of SiO2 in the gas barrier film is large, and the refractive index is less than 1.5.
[0034] The refractive index value of the gas barrier film of this embodiment for light with a wavelength of 550 nm is preferably 1.5 or more. The refractive index value for light with a wavelength of 550 nm is preferably 1.7 or less. Since the refractive index value for light with a wavelength of 550 nm is within the above range, the gas barrier film exhibits a medium refractive index and is suitable for display applications and the like. In this embodiment, the refractive index n and extinction coefficient k for light with a wavelength of 550 nm are measured using a spectrophotometer (SolidSpec-3700, manufactured by Shimadzu Corporation) to measure the spectra of transmission, front surface reflection, and back surface reflection, and n can be calculated from these spectra using the Cauchy formula. k can be calculated from the Sellmeier formula.
[0035] The gas barrier film of this embodiment preferably has no peaks derived from crystals when measured by X-ray diffraction. This gives the gas barrier film an amorphous structure, which reduces the number of conduction paths for moisture and gas between crystals derived from crystallinity, thereby improving the gas barrier properties. In this embodiment, the measurement by X-ray diffraction can be performed using an XRD (XRD-6100, manufactured by Shimadzu Corporation) in accordance with JIS K 0131-1996.
[0036] <Gas barrier film> The gas barrier film according to one embodiment of the present invention comprises, in this order, a substrate, an undercoat layer, and the above-mentioned gas barrier layer. Each of these will be described below.
[0037] (base material) The substrate may be a resin film commonly used in gas barrier films. For example, the substrate may be a plastic film or sheet such as polyethylene terephthalate (PET), cycloolefin polymer (COP), polyethylene (PE), polyimide (PI), polyethylene naphthalate (PEN), polypropylene (PP), polymethyl methacrylate (PMMA), polycarbonate (PC), or polyethersulfone (PES). Among these, the substrate is preferably made of a material having flexibility (pliability) such as a plastic film. This allows the gas barrier film to be suitably used in a wide range of applications, such as electronic device components such as displays.
[0038] The thickness of the substrate is not particularly limited. For example, the thickness of the substrate is preferably 5 μm or more, more preferably 12 μm or more, and even more preferably 23 μm or more. The thickness of the substrate is preferably 250 μm or less, more preferably 125 μm or less, and even more preferably 50 μm or less. When the thickness of the substrate is within the above range, the gas barrier film has excellent handleability and flexibility.
[0039] (base layer) The underlayer is provided on the substrate. The underlayer is provided to prevent defects such as pinholes in the gas barrier film by planarizing the substrate surface, and to improve the interlayer adhesion between the substrate and the gas barrier film. That is, for example, when fine deposits or protrusions are present on the substrate, there is a risk that pinholes will be generated from such deposits when the gas barrier film is formed on the substrate. Therefore, in the gas barrier film of the present embodiment, by forming the underlayer, even if fine deposits or protrusions are present on the substrate, defects caused by such deposits or surface roughness are easily prevented. As a result, the obtained gas barrier film exhibits excellent gas barrier properties.
[0040] The composition of the underlayer is not particularly limited. For example, the underlayer contains 50% by mass or more of inorganic components at the interface with the gas barrier film, and is preferably an inorganic coating material, a modified inorganic coating material, or a mixture of the inorganic coating material and an organic coating material. Such a gas barrier film is less likely to cause defects in the gas barrier film and is likely to exhibit excellent gas barrier properties.
[0041] The inorganic coating material is preferably silsesquioxane, perhydropolysilazane (PHPS), metal alkoxide, etc. The organic coating material is preferably acrylic, acrylic urethane, epoxy, ester, urethane, etc.
[0042] The method of forming the underlayer is not particularly limited. For example, the underlayer containing an organic-inorganic composite oxide can be formed by preparing a solution in which an organic-inorganic oxide is dissolved in an arbitrary solvent, applying (wet coating) (for example, spray coating, bar coating, gravure printing, etc.) to a substrate, and curing or drying. At this time, the surface of the applied solution is flattened by surface tension, so the surface of the obtained underlayer is also flat. More specifically, when forming an underlayer containing silicon oxide, the underlayer can be formed by applying (for example, spray coating) a solution of SiOx or perhydropolysilazane (PHPS) to a substrate and curing by heating. The underlayer made of perhydropolysilazane has Si-H, Si-N, and Si-O bonds. Such an underlayer becomes a layer in which oxidation has progressed by curing in an oxidizing atmosphere, and the interlayer adhesion between the underlayer and the gas barrier film can be further improved. In addition, the underlayer containing polysilazane formed in this manner exhibits excellent flatness and plasma resistance. This makes it possible to form a gas barrier film on the substrate on which the undercoat layer is formed, with less defects such as pinholes. Furthermore, the surface of the formed gas barrier film is also excellent in smoothness. As a result, even when a second gas barrier film is formed on the gas barrier film, defects such as pinholes are less likely to occur.
[0043] In addition, when forming an underlayer that is a gradient film in which the concentration of inorganic components is unevenly distributed in the thickness direction, for example, a solution is prepared by dissolving an organic-inorganic hybrid resin containing silicon alkoxide containing a surfactant component in an arbitrary solvent, and the solution is applied to a substrate, dried, and cured to form a gradient film in which silicon alkoxide is unevenly distributed on the surface of the underlayer. In such a gradient film, silicon components are present in large amounts (for example, 18 at% or more and 40 at% or less) near the interface that contacts the gas barrier film. Meanwhile, organic components are present in large amounts near the interface that contacts the substrate. The surface on the side where inorganic components are present in large amounts can improve interlayer adhesion with the gas barrier film by forming a flat surface. Meanwhile, the surface on the side where organic components are present in large amounts has excellent interlayer adhesion with the substrate, which is also made of organic components.
[0044] Furthermore, a multi-layer underlayer in which an organic film and an inorganic component are laminated can be formed, for example, by providing an underlayer made of an organic component as the underlayer on the side in contact with the substrate, and providing an underlayer made of an inorganic component such as SiOx or perhydropolysilazane as the underlayer on the side in contact with one of the gas barrier films.
[0045] When the inorganic components of the underlayer are measured in the thickness direction of the underlayer from the surface in contact with the gas barrier film toward the substrate by X-ray photoelectron spectroscopy (XPS), the concentration of silicon atoms in the surface in contact with the gas barrier film is preferably 18 at% or more and 40 at% or less. When the concentration of the inorganic components is within the above range, the gas barrier film has excellent plasma resistance and excellent adhesion to the gas barrier film due to the inorganic components present in large amounts on the surface of the underlayer. As a result, the gas barrier film suppresses defects occurring in the gas barrier film and has better interlayer adhesion between the substrate layer and the gas barrier film. In addition, the gas barrier film exhibits even better gas barrier properties. In this embodiment, the concentration of carbon atoms constituting the underlayer is preferably 55 at% or less on the surface in contact with the gas barrier film, and the concentration of the inorganic components in the portion other than the surface (for example, the inside) is not particularly limited. The concentration of silicon atoms in the inside of the underlayer may be 40 at% or more and may be less than 18 at%. The XPS measurement in this embodiment can be performed using an X-ray photoelectron spectrometer (PHI5000 VersaProbe2, manufactured by ULVAC-PHI, Inc.).
[0046] The thickness of the underlayer is not particularly limited. For example, the thickness of the underlayer is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more. When the thickness of the underlayer is 0.1 μm or more, the surface of the underlayer is easily flattened, and pinholes are less likely to occur in the gas barrier film. In addition, the thickness of the underlayer is preferably 20 μm or less, more preferably 5.0 μm or less, and even more preferably 3.0 μm or less. When the thickness of the underlayer is 20 μm or less, cracks due to membrane stress are less likely to occur.
[0047] (Gas barrier film) The gas barrier film is provided on the underlayer and is the same as that described above in the embodiment relating to the gas barrier film.
[0048] The thickness of the gas barrier film is not particularly limited. For example, the thickness of the gas barrier film is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 20 nm or more. The thickness of the gas barrier film is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 100 nm or less. When the thickness of the gas barrier film is within the above range, the gas barrier film can exhibit the desired gas barrier properties.
[0049] The gas barrier film can be formed on the underlayer by a sputtering method. The sputtering method can be, for example, a dual sputtering method or an on-chip sputtering method. Specifically, the gas barrier film can be formed on the underlayer by using the sputtering target described above in relation to the embodiment of the sputtering target.
[0050] The resulting gas barrier film contains the gas barrier layer described above. Therefore, the gas barrier film exhibits a medium refractive index and is suitable for display applications. The water vapor transmission rate of the gas barrier film is 1×10 -1 (g / m 2 / day) or less, and 1×10 -2 (g / m 2 / day) or less is more preferable. When the water vapor transmission rate of the gas barrier film is within the above range, the gas barrier film exhibits excellent gas barrier properties. EXAMPLES
[0051] The present invention will be described in more detail below with reference to the following examples. The present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass".
[0052] <Experimental Examples 1A-1C> Samples having gas barrier films were prepared for various substrates by dual sputtering under the conditions shown in Table 1. In Table 1, O2 partial pressure refers to the ratio of the O2 gas amount (sccm) to the total gas amount (sccm) of Ar gas amount (sccm) and O2 gas amount (sccm).
[0053] <Experiment examples 2A~2C, 3A~3C, 4A~4C, 5A~5C> Samples were prepared in the same manner as in Experimental Examples 1A to 1C, except that the conditions were changed as shown in Table 1. Table 3 shows conversion data for calculating the silicon content. Table 4 shows details of the substrates used in each experimental example. Tables 5 to 9 show the results of compositional analysis such as the silicon oxide content of the obtained samples, and the measurement results of the optical constants. Figures 1 to 4 are graphs showing the results of crystallinity analysis of the obtained samples.
[0054] The composition was analyzed using XRF (Primini, manufactured by Rigaku).
[0055] Crystallinity analysis was performed using an XRD (XRD-6100, manufactured by Shimadzu Corporation).
[0056] [Table 1]
[0057] <Experimental Examples 6A-8C> Using the conditions listed in Table 2 below, samples with gas barrier films were prepared on various substrates by on-chip sputtering. Specifically, gas barrier films were formed on each substrate listed in Table 4 by sputtering. In sputtering, a single cathode was used as the target, and a certain number of 1 cm square silicon (Si) wafers were arranged on a disk-shaped metal target (Al, Ta, W). The ratio of the Si target area to the metal target area was as shown in Table 2. In Table 2, O2 partial pressure refers to the ratio of the O2 gas amount (sccm) to the total gas amount (sccm) of Ar gas amount (sccm) and O2 gas amount (sccm).
[0058] [Table 2]
[0059] [Table 3]
[0060] [Table 4]
[0061] [Table 5]
[0062] In Table 5, SiO2Ratio [vol%] was calculated as follows. First, the X-ray energy intensity of each gas barrier film of Experimental Examples 1A to 4A was measured using a fluorescent X-ray measurement device (XRF (Primini, manufactured by Rigaku)). A calibration curve was created using the thickness of each gas barrier film measured using a contact step gauge and the X-ray energy intensity of each gas barrier film. The XRF film thickness was calculated from this calibration curve. The SiO2Ratio [vol%], SiO2Ratio [wt%], and SiRatio [wt%] were calculated according to the following formulas. The same applies to Tables 6 and 7. SiO2Ratio[vol%]=[{(XRF film thickness_SiO2) / {(XRF film thickness_ZnO)+(XRF film thickness_SiO2)}]×100 Weight (ZnO) = (XRF film thickness_ZnO) x density (ZnO) Weight (SiO2) = (XRF thickness_SiO2) x density (SiO2) ·SiO2Ratio[wt%]=[(Weight(SiO2)) / {(Weight(SiO2))+(Weight(ZnO))}]×100 ·Zn[mol]=(weight(ZnO)) / (molecular weight(ZnO)) ·Si[mol]=(weight(SiO2)) / (molecular weight(SiO2)) ·Si Ratio[mol%]=Si[mol] / {Zn[mol]+Si[mol]}×100 ·Si Ratio[wt%]={Si[mol]×atomic weight (Si)} / {Zn[mol]×atomic weight (Zn)+Si[mol]×atomic weight (Si)}×100
[0063] [Table 6]
[0064] [Table 7]
[0065] [Table 8]
[0066] The calculation formulas for the items in Table 8 are as follows: SiO2Ratio[vol%]=[{(XRF film thickness_SiO2) / {(XRF film thickness_ZnAlO)+(XRF film thickness_SiO2)}]×100
[0067] [Table 9]
[0068] The formulas for calculating each item in Table 9 are as follows. To supplement, first, the content of each metal oxide present in each barrier film of Experimental Example 5A to Experimental Example 8A was measured using an X-ray fluorescence measurement device (XRF (Primini, manufactured by Rigaku)). Then, SiO2Ratio [vol%], SiO2Ratio [wt%], and SiRatio [wt%] were calculated according to the following formulas. ·SiO2Ratio[vol%]=[{(Content(mg / cm 2 )_SiO2) / Density(SiO2)} / {(Content(mg / cm 2 )_Cr2O3) / Density(Cr2O3)+(Content(mg / cm 2 )_SiO2) / density(SiO2)}]×100 ·SiO2Ratio[wt%]=[{(Content(mg / cm 2 )_SiO2)} / {(Content (mg / cm 2 )_Cr2O3)+(Content (mg / cm 2 )_SiO2)}]×100 ·Cr[mol]=(Content (mg / cm 2 )_Cr2O3) / (molecular weight(Cr2O3))×2 ·Si[mol]=(Content (mg / cm 2 )_SiO2) / (molecular weight(SiO2)) ·Si Ratio[mol%]=Si[mol] / {Cr[mol]+Si[mol]}×100 ·Si Ratio[wt%]={Si[mol]×atomic weight (Si)} / {Cr[mol]×atomic weight (Cr)+Si[mol]×atomic weight (Si)}×100
[0069] Tables 5 to 9 also show the values of the refractive index n and extinction coefficient k at a wavelength of 550 nm for the gas barrier films of Experimental Examples 1B to 5B. The refractive index n and extinction coefficient k for light with a wavelength of 550 nm were determined by measuring the spectra of transmission, front surface reflection, and back surface reflection using a spectrophotometer (SolidSpec-3700, manufactured by Shimadzu Corporation), and n was calculated using these spectra according to the Cauchy formula. k was calculated using the Sellmeier formula. In addition, "-" in the optical constants section of Tables 5 to 9 means that no data is available.
[0070] [Table 10]
[0071] In Table 10, the SiO2Ratio [vol%], SiO2Ratio [wt%], and SiRatio [wt%] were calculated according to the following formula. ·SiO2Ratio[vol%]=[{(Content(mg / cm 2 )_SiO2) / Density(SiO2)} / {(Content(mg / cm 2 )_Al2O3) / Density(Al2O3)+(Content(mg / cm 2 )_SiO2) / density(SiO2)}]×100 ·SiO2Ratio[wt%]=[{(Content(mg / cm 2 )_SiO2)} / {(Content (mg / cm 2 )_Al2O3)+(Content (mg / cm 2 )_SiO2)}]×100 ·Al[mol]=(Content (mg / cm 2 )_Al2O3) / (molecular weight(Al2O3))×2 ·Si[mol]=(Content (mg / cm 2 )_SiO2) / (molecular weight(SiO2)) ·Si Ratio[mol%]=Si[mol] / {Al[mol]+Si[mol]}×100 ·Si Ratio[wt%]={Si[mol]×atomic weight (Si)} / {Al[mol]×atomic weight (Al)+Si[mol]×atomic weight (Si)}×100
[0072]
Table 11
[0073] Table 11: Calculate the following formula: SiO2Ratio[vol%], SiO2Ratio[wt%], and Si Ratio[wt%]. ·SiO2Ratio[vol%]=[{(Content(mg / cm 2 )_SiO2) / density(SiO2)} / {(content(mg / cm 2 )_Ta2O5) / density(Ta2O5)+(content(mg / cm 2 )_SiO2) / density(SiO2)}]×100 ·SiO2Ratio[wt%]=[{(Content(mg / cm 2 )_SiO2)} / {(Content (mg / cm 2 )_Ta2O5)+(content (mg / cm 2 )_SiO2)}]×100 ·Ta[mol]=(content(mg / cm 2 )_Ta2O5) / (molecular weight(Ta2O5))×2 ·Si[mol]=(Content(mg / cm 2 )_SiO2) / (molecular weight(SiO2)) ·Si Ratio[mol%]=Si[mol] / {Ta[mol]+Si[mol]}×100 ·Si Ratio[wt%]={Si[mol]×atomic weight(Si)} / {Ta[mol]×atomic weight(Ta)+Si[mol]×atomic weight(Si)}×100
[0074]
Table 12
[0075] In Table 12, the SiO2Ratio [vol%], SiO2Ratio [wt%], and SiRatio [wt%] were calculated according to the following formula. ·SiO2Ratio[vol%]=[{(Content(mg / cm 2 )_SiO2) / Density(SiO2)} / {(Content(mg / cm 2 )_WO3) / Density(WO3)+(Content(mg / cm 2 )_SiO2) / density(SiO2)}]×100 ·SiO2Ratio[wt%]=[{(Content(mg / cm 2 )_SiO2)} / {(Content (mg / cm 2 )_WO3)+(Content (mg / cm 2 )_SiO2)}]×100 ·W [mol]=(Content (mg / cm 2 )_WO3) / (molecular weight(WO3)) ·Si [mol]=(Content (mg / cm 2 )_SiO2) / (molecular weight(SiO2)) ·Si Ratio[mol%]=Si[mol] / {W[mol]+Si[mol]}×100 ·Si Ratio[wt%]={Si[mol]×atomic weight (Si)} / {W[mol]×atomic weight (W)+Si[mol]×atomic weight (Si)}×100
[0076] Tables 10 to 12 also show the values of the refractive index n and extinction coefficient k at a wavelength of 550 nm for the gas barrier films of Experimental Examples 6B to 8B. The refractive index n and extinction coefficient k for light with a wavelength of 550 nm were determined by measuring the spectra of transmission, front surface reflection, and back surface reflection using a spectrophotometer (SolidSpec-3700, manufactured by Shimadzu Corporation), and n was calculated using these spectra according to the Cauchy formula. k was calculated using the Sellmeier formula. In addition, "-" in the optical constants section of Tables 5 to 9 means that no data is available.
[0077] Table 13 shows data extracted from Tables 5 to 12 regarding the relationship between the content (vol %) of silicon oxide (SiO2) contained in the gas barrier films of Experimental Examples 1B to 8B and the refractive index n.
[0078] [Table 13]
[0079] The value of the refractive index n at a wavelength of 550 nm when silicon oxide (SiO2) is 100% by volume is added in Table 13 using the literature value (1.470). A graph of Table 13 is shown in FIG. 5. As shown in Table 13 and FIG. 5, it was confirmed that the content of silicon oxide (SiO2 content) relative to the total amount of metal oxide and silicon oxide is 60 to 90% by volume so that the refractive index n falls within the range of about a medium refractive index (n = 1.5 to 1.7). In addition, Table 14 shows data in which the content of silicon oxide (SiO2) (vol%) in Table 13 is replaced with the value calculated for the content of silicon (Si) (wt%) relative to the total amount of metal and silicon (Si) contained in each gas barrier film in Tables 5 to 12.
[0080] [Table 14]
[0081] In addition, for ZnAlSiO in Table 8, the content (wt%) of silicon (Si) relative to the total amount of metal and silicon (Si) could not be calculated, so it is omitted. In Table 14, as in Table 13, the refractive index n at a wavelength of 550 nm is the refractive index of each gas barrier film. In each gas barrier film, when silicon oxide (SiO2) is 100% by volume, it means that no other metal is contained, so in this case, the content of silicon (Si) relative to the total amount of metal and silicon (Si) is 100% by mass. A graph of Table 14 is shown in Figure 6. As shown in Table 14 and Figure 6, it was confirmed that the silicon content (Si content) relative to the total amount of metal and silicon is 40 to 90% by mass in order for the refractive index n to be within the range of about a medium refractive index (n = 1.5 to 1.7).
[0082] According to the above results, in order to make the SiO2 content in the gas barrier film 60-90 volume %, it was found that it is appropriate to make the silicon content in the sputtering target for forming the gas barrier film by sputtering with O2 introduction 40-90 mass % relative to the total amount of metal and silicon. In other words, by using a sputtering target containing metal and silicon, with the silicon content in the total amount of metal and silicon being 40-90 mass %, and by introducing O2 to form the gas barrier film by sputtering, it is possible to make the refractive index n of the completed gas barrier film in the range of about the medium refractive index (n = 1.5-1.7).
[0083] For ZnAlSiO using Zn-Al as the metal species, there is no calculated value of the silicon (Si) content (wt%) relative to the total amount of metal and silicon (Si). However, referring to FIG. 5, it can be said that the correlation between the refractive index n at a wavelength of 550 nm and the content (vol%) of silicon oxide (SiO2) in the gas barrier film is between that of TaSiO and that of CrSiO when the refractive index n at a wavelength of 550 nm of the gas barrier film is in the range of approximately 1.5 to 1.7. If so, it is presumed that the calculated value of the silicon (Si) content (wt%) relative to the total amount of metal and silicon (Si) for ZnAlSiO is also between that of TaSiO and CrSiO. Therefore, referring to FIG. 6, it is presumed that the silicon content (Si content) relative to the total amount of metal and silicon for ZnAlSiO is 40 to 90 mass% when the refractive index n at a wavelength of 550 nm of the gas barrier film is in the range of approximately 1.5 to 1.7.
[0084] As shown in Figs. 1 to 4, in Experimental Examples 1C and 4C, the peak position of ZnSiO and ZnAlSiO changed as the SiO2 content increased, and the peak disappeared when the SiO2 content exceeded 30%. In Experimental Examples 2C and 3C, the peak of TiSiO and NbSiO appeared as the SiO2 content increased, and the peak disappeared when the SiO2 content increased further. In Experimental Example 5C, the graph of CrSiO was omitted because no crystallization peak was observed. From the above, it was found that the gas barrier film was in an amorphous state (amorphous) in the region where the SiO2 content was 60 mass% or more, where the refractive index was 1.5 to 1.7. In the case of such an amorphous structure, the number of conduction paths for moisture and gas between crystals due to crystallinity was reduced, and it was considered that the gas barrier film had improved gas barrier properties.
[0085] <Examples 1 to 5> A gas barrier film was produced according to the recipe in Table 16, employing the deposition conditions in Table 15 below. Specifically, an underlayer was formed on each substrate in Table 16 by a wet coating method. Then, a gas barrier film was deposited on the underlayer by a sputtering method. In the sputtering, a single cathode was used as a target, and a predetermined number of 1 cm square silicon (Si) wafers were arranged on a disk-shaped metal target (Nb, Zn, Zn-Al). The ratio of the Si target area to the metal target area was as shown in Table 15. In Table 15, the O2 partial pressure indicates the ratio of the O2 gas amount (sccm) to the total gas amount (sccm) of the Ar gas amount (sccm) and the O2 gas amount (sccm). The thickness of the gas barrier film was adjusted to 150 nm.
[0086] The water vapor transmission rate (WVTR) of the obtained gas barrier film was measured by the following evaluation method. The results are shown in Figures 7 to 9. Figures 7 to 9 are graphs showing the relationship between the silicon oxide content and water vapor transmission rate of the obtained gas barrier film. In Table 16, PHPS stands for inorganic coating material (perhydropolysilazane).
[0087] (Water vapor transmission rate) Gas barrier films having an underlayer and a gas barrier film in order were prepared for various substrates. Specifically, underlayers were formed for various substrates listed in Table 16 by a wet coating method. Then, a gas barrier film was formed on the underlayer under the conditions of Table 15 by using a sputtering method. The coating material of the underlayer in Examples 1, 2, and 4 was an organic-inorganic hybrid coating material (acrylic urethane-based + modified metal alkoxide). The underlayer in Examples 3 and 5 had a two-layer structure with Si801 on the substrate side and PHPS (perhydropolysilazane) on the gas barrier film side. In Table 16, Si801 represents SIkoto801 manufactured by Momentive, and the thickness was set to 183 nm. PHPS represents Aquamica NL 110A-10 manufactured by Merck, and the thickness was set to 70 nm. The coating method was a wet coating method in all cases.
[0088] The water vapor transmission rate (WVTR) of the obtained gas barrier film was measured under conditions of a temperature of 40° C. and a relative humidity of 90% using the cup method (JIS Z 0208-1976).
[0089] [Table 15]
[0090] [Table 16]
[0091] As shown in FIGS. 7 to 9, the water vapor transmission rates of the gas barrier films of Examples 1 to 5 of the present invention are all approximately 10 -2 (g / m 2 / day). In particular, the gas barrier property of the ZnAlSiO in the gas barrier films of Examples 4 and 5 improved with an increase in the SiO2 content. In addition, between the crystalline region indicated by the double-headed arrow in the graph and the other region (amorphous region), the amorphous region had better gas barrier property.
[0092] <Examples 6 to 10> An undercoat layer was formed on each of the various substrates shown in Table 17 below. Then, a gas barrier film was formed on the undercoat layer using a sputtering method under the conditions shown in Table 15. The coating material of the undercoat layer in Examples 6 to 10 was an organic-inorganic hybrid coating material (acrylic urethane-based + modified metal alkoxide). The coating method was a wet coating method in all cases.
[0093] As shown in Table 17 below, WVTR was measured using DELTAPERM (Technolox, a water vapor transmission rate measuring device using differential pressure method), which has higher measurement accuracy. The measurement conditions for WVTR using DELTAPERM were a temperature of 40°C and a relative humidity of 90%. DELTAPERM uses a method (differential pressure method, ISO15106-5) that uses the property that water vapor at a set temperature and humidity is poured into one side of a sample and the other side is evacuated, whereby the pressure inside the cell on the opposite side increases due to the water vapor passing through the sample surface due to the pressure difference, to measure the rate of increase in velocity and calculate the transmission rate.
[0094] [Table 17]
[0095] As shown in Table 17, the gas barrier films of Examples 6 to 10 had a viscosity of about 1.0 × 10 -3 g / m 2 / day or less, demonstrating the high gas barrier properties required for display applications such as organic electroluminescence (EL) and electronic paper.
Claims
1. Contains a metal oxide and a silicon oxide, The content of the silicon oxide relative to the total amount of the metal oxide and the silicon oxide is 60 to 90 volume %, The metal constituting the metal oxide includes any one selected from the group consisting of Zn, Ti, Nb, Al, Ta, W, Cr, and Zn-Al, When measured by X-ray diffraction, there were no peaks derived from crystals. A gas barrier film having a refractive index of 1.5 to 1.7 for light having a wavelength of 550 nm.
2. A gas barrier film comprising a substrate, an undercoat layer, and the gas barrier film according to claim 1 in this order.
3. The water vapor transmission rate is 1×10 -1 (g / m 2 3. The gas barrier film according to claim 2, wherein the gas barrier film has a thermal expansion coefficient of 100 / day or less.
Citation Information
Patent Citations
Manufacturing method for barrier film and plasma CVD equipment used therefor
JP2005219427A
Transparent oxide film and method of producing the same
JP2013189657A
Sputtering target for forming transparent oxide film, and method for production thereof
JP2013213268A
Gas barrier laminate, and manufacturing method thereof
JP2020114667A
Gas barrier laminate and method for producing the same
JP2021000817A